2017
DOI: 10.3847/1538-4357/aa9180
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Diffuse Dwarf Galaxy Candidates around M101

Abstract: We have conducted a search of a 9 deg 2 region of the CFHTLS around the Milky Way analog M101 (D∼7 Mpc), in order to look for previously unknown low surface brightness galaxies. This search has uncovered 38 new low surface brightness dwarf candidates, and confirmed 11 previously reported galaxies, all with central surface brightness µ(g,0)>23mag/arcsec 2 , potentially extending the satellite luminosity function for the M101 group by ∼1.2 magnitudes. The search was conducted using an algorithm that nearly autom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
108
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 78 publications
4
108
0
1
Order By: Relevance
“…In the current work we present HST results for 19 of the dwarf candidates reported by Bennet et al (2017), four of which were first identified by Karachentsev et al (2015). We list these objects in Table 1 and 2.…”
Section: Dwarf Candidates Around M 101mentioning
confidence: 99%
See 3 more Smart Citations
“…In the current work we present HST results for 19 of the dwarf candidates reported by Bennet et al (2017), four of which were first identified by Karachentsev et al (2015). We list these objects in Table 1 and 2.…”
Section: Dwarf Candidates Around M 101mentioning
confidence: 99%
“…Meanwhile the other 17 targets appear as unresolved diffuse emission, indicating that the TRGB is too faint to be detected in our HST imaging, and that they are in the background. Beyond this, there are a further 23 diffuse dwarfs from Bennet et al (2017) that were not imaged with HST, and we statistically assess their M101 membership status in Section 4.3. The spatial distribution of all of the resolved and diffuse dwarfs around M101 are shown in Figure 1.…”
Section: The Dwarf Candidate Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies confirmed in total 8 satellites for this galaxy with the faintest having a V-band absolute magnitude of M V = −8.2 mag. Most of these candidates have been found in a wide survey using also the CFHT byBennet et al (2017) and some of them byMerritt et al (2014),Javanmardi et al (2016), andMüller et al (2017b). These surveys cover almost isotropically the 260 kpc virial radius of M101 (seefigure 1inCarlsten et al 2019b).…”
mentioning
confidence: 99%